<h3><u>Answer:</u></h3>
<h3>
<u>Solution:</u></h3>
We are given that the arithmetic progression is defined by :
➝ 2n + 1
<em>Therefore, </em>
- <u>For </u><u>first </u><u>term</u>
➙ n = 1
➝ 2 × 1 + 1
➝ 2 + 1
➝ 3
- <u>For </u><u>second </u><u>term</u>
➙ n = 2
➝ 2 × 2 + 1
➝ 4 + 1
➝ 5
- <u>Common </u><u>difference</u>
➙ 2nd term - 1st term
➝ 5 - 3
➝ 2
<h3><u>More </u><u>information</u><u>:</u></h3>
- The difference between the successive term and the preceding term is the difference of an arithmetic progression. It is always same for the same arithmetic progression.
Remainder Theorem says that if there is any Polynomial equation P(x), which is to be divided by (x - a) then remainder can be calculated by substituting value of a in equation P(x).
= P(x) divided by ![(x+2)](https://tex.z-dn.net/?f=%28x%2B2%29)
Step 1: Find a
To find a we will have to convert (x+2) into (x - a) form
i.e. (x+2) = (x - (-2))
therefore, a = -2
Step 2: Substitute value of a in P(x),
By substitution we get,
![2(-2)^{4}+(-2)^{2}-10(-2)-1](https://tex.z-dn.net/?f=2%28-2%29%5E%7B4%7D%2B%28-2%29%5E%7B2%7D-10%28-2%29-1)
= ![2(16) + 4 +20 -1](https://tex.z-dn.net/?f=2%2816%29%20%2B%204%20%2B20%20-1)
= ![32 +4 + 20 - 1](https://tex.z-dn.net/?f=32%20%2B4%20%2B%2020%20-%201)
=
= Remainder
Hence, Remainder is 55.
Answer:
B
Step-by-step explanation:
it's basically 2+7
Answer:
x = 36
Step-by-step explanation:
A= 320 cm2 and that is the answer